BACTERIAL CONTAMINATION OF EXTERNAL SURFACE OF COCKROACHES AND THEIR ANTIBIOTIC RESISTANCE IN HOSPITALS OF HAMADAN, IRAN - Nazari, Sasan -; Habibi, Farasat -; Nazari, Saman -; Hosseini, Seyed Mostafa -; Nazari, Mansour - (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine the type of cockroaches contaminated by bacterial species and their antibiotic resistance in different hospitals of Hamadan city. Methodology: This cross sectional study was carried out on 179 samples of cockroaches collected from hospitals in Hamadan city, Iran. The body surface was washed with physiological sterile serum and the the solution was centrifuged at 2000 rpm for five minutes. bacteria were identified using the phenotypic method. Antibiotic resistance of bacteria against various antibiotics was checked with disk diffusion method. Data were analyzed using SPSS version 20 software. chi-square test was applied for significance. P value <0.05 was regarded as significant. Results: Out of 179 cockroaches, 117 (65.36%) and 62 (34. 64%) were American and German cockroaches respectively. In total, 173 (96. 64%) of them were contaminated with bacteria. Three hundred and fourteen (76%) and 99 (24%) strains of bacteria were isolated from both types of cockroaches. E. coli was the most common (119 cases) and Morganella was the lowest species found. Gram positive bacteria showed the highest antibiotic resistance to Clindamycin with 106 (79.7%) and Tetracycline with 43 (32.33%) highest susceptibility. Gram-negative bacteria had the highest resistance to Amoxicillin and the highest sensitivity to Norfloxacin. Conclusion: Bacterial contamination of cockroaches in hospital environment is an important concern in health care systems. Moreover, antibiotic resistance observed in separated bacteria can enhance the pathogenicity of bacteria.